2009
DOI: 10.1111/j.1365-313x.2009.04045.x
|View full text |Cite|
|
Sign up to set email alerts
|

CBL-mediated targeting of CIPKs facilitates the decoding of calcium signals emanating from distinct cellular stores

Abstract: SUMMARYDuring adaptation and developmental processes cells respond through nonlinear calcium-decoding signaling cascades, the principal components of which have been identified. However, the molecular mechanisms generating specificity of cellular responses remain poorly understood. Calcineurin B-like (CBL) proteins contribute to decoding calcium signals by specifically interacting with a group of CBL-interacting protein kinases (CIPKs). Here, we report the subcellular localization of all 10 CBL proteins from A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

20
299
0
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 249 publications
(322 citation statements)
references
References 32 publications
20
299
0
3
Order By: Relevance
“…Not only the expression pattern, but the subcellular localization of CBL-type calcium sensors is also believed to reflect spatial specification of Ca 2+ signaling [8,28]. In this study, we confirmed that CBL2 and CBL3 are specifically associated with the tonoplast in Arabidopsis cells, consistent with an earlier study using N. benthamiana [28].…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…Not only the expression pattern, but the subcellular localization of CBL-type calcium sensors is also believed to reflect spatial specification of Ca 2+ signaling [8,28]. In this study, we confirmed that CBL2 and CBL3 are specifically associated with the tonoplast in Arabidopsis cells, consistent with an earlier study using N. benthamiana [28].…”
Section: Discussionsupporting
confidence: 81%
“…In this study, we confirmed that CBL2 and CBL3 are specifically associated with the tonoplast in Arabidopsis cells, consistent with an earlier study using N. benthamiana [28]. We also further demonstrated that the N-terminal 19-aa of the CBL2 protein defines a tonoplast targeting sequence (TTS) that is necessary and sufficient for subcellular localization to the vacuolar membrane.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations